THE ROLE OF INDEPENDENT EDUCATION IN PREPARING STUDENTS FOR INNOVATIVE ACTIVITIES AND THE METHOD OF CONDUCTING THEM - Suyunova, Yulduz Ahmadovna (Educational Research in Universal Sciences, 2023)
Today, the process of training a qualified specialist cannot be imagined without independent education. Because it is in the process of doing independent work that students develop critical and creative thinking reflexes. Independent learning activity is important in mastering knowledge in any academic subject. Training in the classroom cannot fully provide students with high-level knowledge. In the implementation of this, independent educational activity serves as a supplemental developer.